2017
DOI: 10.1002/2017sw001693
|View full text |Cite
|
Sign up to set email alerts
|

Possible Cause of Extremely Bright Aurora Witnessed in East Asia on 17 September 1770

Abstract: Extremely bright aurora was witnessed in East Asia on 17 September 1770, according to historical documents. The aurora was described as “as bright as a night with full moon” at magnetic latitude of 25°. The aurora was dominated by red color extending from near the horizon up beyond the polar star (corresponding to elevation angle of ~35°). We performed a two‐stream electron transport code to calculate the volume emission rates at 557.7 nm (OI) and 630.0 nm (OI). Two types of distribution of precipitating elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 43 publications
3
42
0
Order By: Relevance
“…In order for these aurorae to be visible at Inami up to 10° in elevation angle (see, e.g., Shiokawa et al, ), the equatorward boundary of the auroral oval needs to be down to, at least, 37.6° ILAT, assuming an auroral elevation up to 400 km (Ebihara et al, ; Silverman, ). This means the equatorward boundary of the auroral oval was at least extending beyond the zenith of Nertschinsk (40.0° MLAT) during the period of auroral visibility in China and Japan.…”
Section: Auroral Evolutions and Magnetic Disturbancesmentioning
confidence: 99%
“…In order for these aurorae to be visible at Inami up to 10° in elevation angle (see, e.g., Shiokawa et al, ), the equatorward boundary of the auroral oval needs to be down to, at least, 37.6° ILAT, assuming an auroral elevation up to 400 km (Ebihara et al, ; Silverman, ). This means the equatorward boundary of the auroral oval was at least extending beyond the zenith of Nertschinsk (40.0° MLAT) during the period of auroral visibility in China and Japan.…”
Section: Auroral Evolutions and Magnetic Disturbancesmentioning
confidence: 99%
“…Besides, Vaquero et al () report a possible case of sporadic aurora in Mexico on 19 April 1843. We point out also that, to our knowledge, there are no reports in Mexico of the low‐latitude red aurora registered in Asia in September 1770 (Ebihara et al, ; Hayakawa et al, ; Kataoka & Iwahashi, ; Nakazawa et al, ; Willis et al, ) nor for the aurora in October 1870 (Vaquero et al, ).…”
Section: Observations Of the 1859 Aurora In Mexicomentioning
confidence: 67%
“…We calculated the 2D distribution of the auroral volume emission rates at 630.0 nm and 557.7 nm. The simulation scheme is the same as that performed by Ebihara et al (2017), except that the flux of precipitating electrons was multiplied by 10, and the precipitation of the electrons was assumed to occur between 29° and 32° ILATs. The Spectrum B of precipitating electrons (Ebihara et al 2017) was used to calculate the volume emission rate of the aurora, which corresponds to the HILEEs observed by the DMSP F8 satellite at 0130:08 UT on 14 March 1989 (Dst value of −589 nT).…”
Section: Auroral Extent and Scale Of The Magnetic Stormmentioning
confidence: 99%
“…This event even possibly rivaled the Carrington event. It has recently been reported that in 1770, a great sunspot at least twice as large as the one during the Carrington event possibly resulted in a series of great magnetic storms causing extremely bright low-latitude auroras visible down to 18.8° MLAT in association with precipitation of high-intensity low-energy electrons (HILEEs) to the upper atmosphere (Ebihara et al 2017;Hayakawa et al 2017e).…”
mentioning
confidence: 99%